Sexual and relationship satisfaction associated with shifts in dyadic trajectories of depressive symptoms in German couples across four years. - Morgan, Preston Christopher (Kansas State University, 2017)
Depression is a pervasive mental health concern; thus, it is important to identify modifiable risk factors associated with reducing depressive symptoms across time. Using 1,946 married and cohabiting German couples assessed annually across 4 years from the Panel Analysis of Intimate Relationships and Family Dynamics (Pairfam) study, we tested if shifts across time in sexual satisfaction and relationship satisfaction were linked with expected shifts in trajectories of depressive symptoms using dyadic time-varying covariate growth models. For both men and women, higher sexual and relationship satisfaction scores across time were significantly associated with decreasing their own depressive symptom trajectories across time, but only relationship satisfaction was linked with a shift in their partners’ trajectories of depressive symptoms. Potential clinical implications from these results include the treatment of depressive symptoms by making changes across time in their own relationship satisfaction and sexual satisfaction.
Keywords: Depressive symptoms; Depressive symptom trajectories; Relationship satisfaction; Sexual satisfaction